2018
DOI: 10.1007/s11663-018-1391-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Void Formation in Cu/Sn-Sn/Cu System During Transient Liquid Phase Bonding Process Through Diffusion Modeling

Abstract: Transient Liquid Phase (TPL) bounding of Sn foil sandwiched between two Cu foils involves, in the temperature range above the melting point of Sn (232°C) and below 350°C, the formation and the growth of two intermetallic compounds (IMCs) Cu6Sn5 and Cu3Sn and mostly unintended micro-pores. The present study aims to analyze the mechanism of void development during the soldering process through an experimental and modeling approach of diffusion controlled IMC transformation. This modeling couples the diffusion pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…The microstructural, elemental, and chemical analysis of the Cu-SAC bonding via the TLP process and previous studies were then correlated to propose a bonding mechanism, including the Cu3Sn coated layer effect. Note that the following mechanisms rely on the experimental analysis presented in this paper and previously published kinetics and thermodynamics simulations [8]. The simulations are based upon Fick's diffusion law of the different elements and phases present in the bonding process and corroborated to interfacial mass transport equations.…”
Section: The Bonding Mechanism Of Cu-sac Joints Having or Not The Cu3...mentioning
confidence: 86%
See 1 more Smart Citation
“…The microstructural, elemental, and chemical analysis of the Cu-SAC bonding via the TLP process and previous studies were then correlated to propose a bonding mechanism, including the Cu3Sn coated layer effect. Note that the following mechanisms rely on the experimental analysis presented in this paper and previously published kinetics and thermodynamics simulations [8]. The simulations are based upon Fick's diffusion law of the different elements and phases present in the bonding process and corroborated to interfacial mass transport equations.…”
Section: The Bonding Mechanism Of Cu-sac Joints Having or Not The Cu3...mentioning
confidence: 86%
“…It was observed that the Cu6Sn5 grows into a rounded grains morphology called scallops from both Cu/Sn bonding interfaces [15]. Later, such grains development led to a Cu6Sn5 impingement before the total Sn consumption, thus forming pores in the solder joint [2,8,16]. Naturally, pores degrade the IMC's thermal and mechanical properties and deteriorate its reliability [17].…”
Section: Introductionmentioning
confidence: 99%
“…By (8), for the reaction (5) between Sn and Cu the ratio of volumes we find J tr ¼ 1:44 (44% volume expansion) if n ¼ 0 (solid skeleton approach) and J tr ¼ 0:92 (8% volume shrinkage) if n ¼ À1. To our knowledge the question about the value of the transformation strain accompanying IMC formation remains open and estimates of the relative volume change are in the range from À10%, 13,29,30 up to þ44%. 31,32 Further we fit model parameters for n ¼ À0:5, which corresponds to volume ratio J tr ¼ 1:18.…”
Section: Chemical Affinity Tensor and General Problem Statementmentioning
confidence: 99%
“…where x n is given by (30). The solution of the diffusion problem finally gives the concentration at the reaction front as a function of the reaction front position…”
Section: Analytical Solution Of a Model Problemmentioning
confidence: 99%
“…Among others, we can mention the solidification of pure liquid processes where energy diffusion is the main driving force, or precipitation/dissolution processes in multi-component systems involving a solid/liquid or a solid/solid interface where mass transport by diffusion has a large impact on microstructure evolutions. This is case in metallurgy during solid state annealing processes, where phase transformations have to be controlled in order to obtain the volume fraction of phases optimizing the mechanical properties [1,2]; and also during transient liquid phase phenomena involving diffusion-induced solidification, leading in some cases to detrimental pore formation [3,4]. In this broad field of diffusion processes involving complex coupling of driving forces, we focus in this paper on the particular case of diffusion-controlled phase transformations involving diffusion of components at constant temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%